PELATIHAN ASESSMENT/EVALUASI PEMBELAJARAN SEBAGAI PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU DI SMAN 1 CANDUANG KECAMATAN CANDUANG KABUPATEN AGAM - Hefni,; Nilda Elfemi,; Bella Yolanda,; Hanadia Marfita,; Shakila Amanda, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Improving the quality of education is an absolute thing and is the shared responsibility of all parties, especially teachers and school principals. To achieve good quality education, high competence is needed from the education providers, especially teachers as elements that are directly connected to students as the main object of education itself. However, in its implementation, there are still several obstacles which are reflected in the lack of professionalism of teachers in: (1) Making lesson plans, (2) Mastering learning methods, and (3) In evaluating learning outcomes. In this regard, the learning evaluation will be the focus of the service that will be carried out. The activity carried out is to train teachers in the field of assessment / evaluation of learning. The purpose of this service activity is to provide training to teachers at SMAN 1 Canduang, Canduang District, Agam Regency, West Sumatra so that they have the skills, knowledge and attitudes in conducting the evaluation process in accordance with the fields/learning materials they teach. Based on the problems above, it is necessary to carry out a service activity in the form of training in order to improve the professional competence of teachers in terms of implementing learning evaluations, especially related to the manufacture and analysis of evaluation tools. To increase the knowledge capacity and professional skills of teachers in evaluating this learning, training is carried out with the following steps: (1) Preparation, namely coordinating and identifying the needs of training participants, (2) Preparation of mapping training materials by means of FGDs among teams/service members, (3) implementing activities